2011
DOI: 10.1007/s11695-011-0582-z
|View full text |Cite
|
Sign up to set email alerts
|

Mid-term Effects of Sleeve Gastrectomy on Calcium Metabolism Parameters, Vitamin D and Parathormone (PTH) in Morbid Obese Women

Abstract: Postoperative values of vitamin D show a progressive increase, while PTH ones present a significant reduction, without any impact on serum calcium levels. We have demonstrated an inverse correlation between weight loss and vitamin D increase at the third month after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 22 publications
3
22
0
1
Order By: Relevance
“…According to the literature, the level of PTH in the blood after bariatric surgery can change in the direction of its decrease or increase [25][26][27]. In our study, we note a signifi cant decrease in PTH levels starting from the 3rd month of observation, which is in weak negative correlation with VTD, BMI and FAT.…”
Section: Discussionsupporting
confidence: 61%
“…According to the literature, the level of PTH in the blood after bariatric surgery can change in the direction of its decrease or increase [25][26][27]. In our study, we note a signifi cant decrease in PTH levels starting from the 3rd month of observation, which is in weak negative correlation with VTD, BMI and FAT.…”
Section: Discussionsupporting
confidence: 61%
“…After diet-and exercise-induced weight loss, both increased 9-11 and unaltered 12,13 circulating levels of 25OHD have been reported. Likewise, after major weight loss by bariatric surgery, both temporary 14-16 and long-term increases [16][17][18] in circulating levels of 25OHD have been reported, along with reports of no changes one year after surgery. 13,19 Taken together, these findings indicate that body weight is an important factor for circulating 25OHD levels.…”
mentioning
confidence: 97%
“…DIET, SUPPLEMENTS, AND FOODS IN THE MANAGEMENT OF VISCERAL OBESITY [26,28,30]. Our own experience showed that about a quarter of the patients who reported taking supplements developed micronutrient deficiencies [28].…”
Section: Micronutrient Supplementationmentioning
confidence: 84%
“…Interestingly, some studies showed that bariatric surgery can increase 25(OH)D serum concentrations or decrease the frequency of vitamin D deficiency [26,28,29]. This might be explained by the fact that the reduction in adiposity caused by surgery potentiates the bioavailability of vitamin D. This observation should be addressed in further studies.…”
Section: Vitamin D and Calciummentioning
confidence: 95%
See 1 more Smart Citation